How to Mitigate Negative Attitudes Toward the LGBTQ+ Community: A comparative study using the Structured Democratic Dialogue process - Habes, Hasan; Björkqvist, Kaj; Andreou, Andreas (Technium Social Sciences Journal, 2023)
The article discusses the outcomes of two Structured Democratic Dialogues (SDD) held in Padua, Italy and Vaasa, Finland respectively, with the aim of exploring how to mitigate the negative attitudes and atmosphere toward the LGBTQ+ community in these two regions. The participants identified key areas for altering the negative attitudes and creating a positive atmosphere toward the LGBTQ+ community and suggested 77 action plans in Padua, Italy and 31 in Vaasa, Finland. The study reveals that both groups of participants emphasized the importance of education, media representation, and legal protection to combat negative attitudes and promote acceptance of the LGBTQ+ community. However, due to the differences in the national legal systems, the Padua participants placed more emphasis on legal reforms, whereas the Vaasa participants focused more on cultural and educational action plans.